Genetic Engineering - Sithole-Niang, Idah (IntechOpen, 2013)
The book, while having only five chapters, covers a wide range of topics in genetic engineering of microorganisms, plants and animals. Specifically it covers both the natural and social sciences. In the natural sciences topics ranging from the genetic engineering of microorganisms to produce antibiotics, the gene targeting and transformation in plants, the generation of marker-free plants in response to biosafety concerns, as well as the generation of transgenic animals and those derived through cloning are covered. In the social sciences, the issue of ethics in biotechnology and the role of the media in reporting around the cloned sheep, Dolly are discussed.